New Islamic Schools Tradition, Modernity, and Class in Urban Pakistan - Riaz, S. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
The first ethnographic study of the trend toward religious, parochial schooling in urban Pakistan, this book provides data from over fifty-Karachi area schools to establish the complex reasons middle- and upper-class families enroll in religious Islamic schools.